Multipurpose table using knockdown concept / Che Zulkhairi Iswandi Che Hamid - Che Hamid, Che Zulkhairi Iswandi (2013)
This study was conducted to investigate the importance of multipurpose furniture using knockdown concept. The data was analysed based on the questionnaire that had been distributed to 60 correspondences. Most of correspondent give positive feedback to the material used, space saving multifunction concept, suitability of product to everyone and marketable of the product. Overall, the multifunction table using knockdown concept is well accepted by most of the correspondence since it provides benefits to the consumers.